2016
DOI: 10.1016/j.daach.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Archaeoastronomical experiments supported by virtual simulation environments: Celestial alignments in the Antinoeion at Hadrian's Villa (Tivoli, Italy)

Abstract: The archaeological site at Hadrian's Villa (Tivoli, Italy) conventionally called the Antinoeion was used as a testbed for studying the utility of simulation environments for archaeoastronomical research. The site consists of a sanctuary with three temples facing an open plaza which may, or may not, have had an obelisk in the center. Two reconstruction models were made of the site using AutoCAD and 3D Studio Max. In one version, the obelisk was present; in the other, there was no obelisk. The models were import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The simulation of -and walking inside-a 3D scenery under the artificial sky of past times inside Stellarium with all its astronomical features and details opens up new ways of interactive investigation in archaeoastronomy and -in the same applicationcreation of accurate illustrations for dissemination of valid results (Frischer et al, 2016). The approach of loading a 3D model in a well-known 3D model format (Wavefront OBJ) in Stellarium, and free availability of Stellarium, should be easy enough to be applied more frequently also just for research purposes.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation of -and walking inside-a 3D scenery under the artificial sky of past times inside Stellarium with all its astronomical features and details opens up new ways of interactive investigation in archaeoastronomy and -in the same applicationcreation of accurate illustrations for dissemination of valid results (Frischer et al, 2016). The approach of loading a 3D model in a well-known 3D model format (Wavefront OBJ) in Stellarium, and free availability of Stellarium, should be easy enough to be applied more frequently also just for research purposes.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The current version (as of Stellarium 0.18) can load a model in the Alias Wavefront OBJ format including textures and normal mapping, load a separate "walking ground" layer which controls the eye position (Zotti, 2016), and even has the ability to show parts of the model only when they fit to the time currently simulated in the sky , so that the evolution of a multi-phase site like Stonehenge can be experienced without having to interrupt the simulation to load separate models for the various phases described in the literature (Darvill, Marshall, Parker Pearson, & Wainwright, 2012). This open-source 3D rendering system therefore allows virtual walks through landscapes and buildings combined with a high quality astronomical simulation that provides application possibilities from orientation studies to analysis of light-and-shadow interaction like the particular solar illumination of a statue or painting by a spot of sunlight cast through a window on an associated festival day (Frischer, Zotti, Mari, & Vittozzi, 2016). Our largest model so far consisted of 14 million triangles created from a laser scan, which is still shown ZOTTI & NEUBAUER, 2019 at interactive frame rates with shadows on a middleclass notebook PC (with NVidia Geforce 960M).…”
Section: D Simulationmentioning
confidence: 99%
“…The Scenery3D plugin is slowly gaining attention, but while astronomical research data can usually be found online shortly after collection, high-resolution geodata, and more importantly archaeological and cultural heritage data, usually cannot just be downloaded, reconfigured and re-published in a different research context for free, but are stored away in the archives of its creators or their customers, or shown online in a format or with restrictive licensing that prevents download or further use. After the ASTROSIM project (Zotti and Neubauer 2012) and the study of the "Antinoeion" in Hadrian's Villa at Tivoli (Frischer et al 2016), the first author (GZ) was asked for assistance in further projects which were welcome as stress tests with real-world data.…”
Section: Example 1: Vienna Sterngartenmentioning
confidence: 99%
“…The simulation was also presented as an outreach feature on the project website, but, unfortunately, since it was created, Unity web browser plugins have been abandoned in favor of a unified WebGL-based solution. Frischer et al [2016] have presented a study in which the so-called "Antinoeion" in the Villa of Roman emperor Hadrian in Tivoli was placed in these two different virtual environments, the Unity-based environment developed earlier [Frischer and Fillwalk 2012], and the meanwhile published Scenery3D rendering module in Stellarium [Zotti 2015]. One motivation in doing this was for purposes of validation: since the altazimuthal data was calculated differently in each solution, it was interesting to investigate whether the results would be-as hoped-the same.…”
Section: Serious Gaming For Archaeoastronomical Researchmentioning
confidence: 99%
“…Screenshot from Stellarium V0.20.0. Model from Frischer et al [2016] courtesy Matthew R. Brennan and Bernard Frischer (Indiana University).…”
Section: Serious Gaming For Archaeoastronomical Researchmentioning
confidence: 99%